Perancangan Sistem Informasi Pembayaran Syahriah Berbasis Web di Pondok Pesantren Nurul Hidayah Pusat - Khidir Ali Aziz; Bagas Setiyaki Wicaksono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Information technology in Indonesia has developed so rapidly. Therefore, fast, accurate and reliable information is the most important part of human life today. At the Central Nurul Hidayah Islamic Boarding School located in Bogor, Syahriah payments are still made in the conventional way, what is meant by syahriah is monthly payment. From this case, a website-based sharia payment information system is needed using the Waterfall method as a system development method. Based on the analysis of research and discussions that have been carried out, namely providing a website-based sharia payment information system that is integrated and can minimize the loss of payment data that has been made and presents an information system that can display payment data and remaining payments in real time and can print reports according to the period. selected time.